Analisis Manajemen Risiko pada Jasa Mesin Bordir di Usaha Arsel Bandung - Nuri Triani Anggraeni; Ai Malita Wulandari; Intan Nur’aini; Nayla Rubayyina Nugraha; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of embroidery services in the garment industry in Bandung is significant, garnering government attention as a driver of the country's economy. However, this sector has not yet become an independent sector and a pillar of the national economy. This study aims to determine the risks inherent in the embroidery services sector, as its operational activities pose various potential risks, both operationally, financially, and through human resources. The embroidery business is part of the Micro, Small and Medium Enterprises (MSMEs) sector. interviews, and documentation of service business owners and employees. Promotion is carried out through approaches between businesses, or clothing businesses that collaborate with embroidery services. This is because, in the embroidery service environment, there are several businesses producing clothing, jackets, and Levi's pants. The results of the study indicate that the main risks faced include the risk of machine damage, delays in orders, fluctuations in material prices, and dependence on skilled labor. Strategies implemented to control these risks include conducting routine machine maintenance and establishing intensive communication with customers